The Impact of International Outsourcing on the Skill Structure of Employment: Empirical Evidence from German Manufacturing Industries - Markus Diehl (Kiel Institute of World Economics (IfW), 1999)
In recent publications it has been argued that the change of the skill structure of industrial employment is caused by biased technical progress rather than by increasing international trade with low wage countries. However, in linking prices for final goods with prices of primary factors, most empirical studies have only dealt with international trade in final goods and have thereby neglected the impact of international outsourcing. In this paper it is argued that outsourcing can be understood as a substitution of imported intermediate inputs for domestic value added, and that such substitution may have an impact on the skill structure of domestic employment in favor of skilled labor. The empirical evidence for German manufacturing industries supports this hypothesis.
Keywords: F10; J31; 330; International Outsourcing; Trade; Wages; Employment.; Outsourcing; international; Faktorproportionentheorem; Faktorpreisausgleich; Lohnstruktur; Qualifikation; Berufsstruktur; Industrieller Strukturwandel; Importsubstitution; Kostenfunktion; Beschäftigungseffekt; Schätzung; Deutschland